Akalikai in Modern Tamil Literature - Venugopal, Sababathy (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2006)
Akalikai, Modern Tamil Literature, Tamil Poetry அகலிகை, நவீன தமிழ் இலக்கியம், தமிழ் கவிதை